2001
DOI: 10.1021/la0111607
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Micellization of Sodium Alkyl Sulfates in Water at High Temperature and Pressure

Abstract: Apparent molar volumes V Φ ,S were determined for sodium octyl, decyl, and dodecyl sulfates in water at 2 and 19 MPa from 25 to 130 °C. The shapes of V Φ ,S vs the surfactant concentration curves depend on the surfactant alkyl chain, temperature and pressure. The standard partial molar volumes were calculated from data in the premicellar region whereas the partial molar volumes of the surfactant in the micellar phase were obtained from data in the postmicellar region. The partial molar expansibility and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…This fact has been previously reported in the literature as deviation from linearity for surfactants with shorter chain length [75]. This magnitude also decreases with temperature, de Lisi et al [76] finding negative slopes for V φ of sodium octyl, decyl, and dodecyl sulfates in water against temperature in the range 25 • to 130 • C at different pressures, attributing this negative slope value to the expansibility of the surfactant in the micellar state being smaller than that in the aqueous phase. Attwood et al [77] found this decrease with temperature for chlorpromazine, an effect which has been attributed to the dehydration of the ionic head group.…”
Section: Densities and Molar Apparent Volumesmentioning
confidence: 51%
“…This fact has been previously reported in the literature as deviation from linearity for surfactants with shorter chain length [75]. This magnitude also decreases with temperature, de Lisi et al [76] finding negative slopes for V φ of sodium octyl, decyl, and dodecyl sulfates in water against temperature in the range 25 • to 130 • C at different pressures, attributing this negative slope value to the expansibility of the surfactant in the micellar state being smaller than that in the aqueous phase. Attwood et al [77] found this decrease with temperature for chlorpromazine, an effect which has been attributed to the dehydration of the ionic head group.…”
Section: Densities and Molar Apparent Volumesmentioning
confidence: 51%
“…Moreover, it illustrates the dependence on temperature of both the contributions for the aggregates formation and the shift of the micellization equilibrium (equation (6)). The aggregation process involves a decrease of E U in agreement with the hydrophobic desolvation as it occurs for conventional surfactants [46]. Therefore, the constant E U in the low and the high temperature domains reflect the E m and E M values, respectively.…”
Section: Expansibilities Prediction As Functions Of Temperature and Cmentioning
confidence: 94%
“…Considering the electrostatic interactions between Tb(III) and alkyl-sulfate chains, the interactions with water must also be taken into account. In support of this, SDeS shows a higher solubility in water than SDS, and the stronger interactions with this surfactant can also be seen through various thermodynamic properties [27,28].…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 96%